Landscapes, Archaeology, and the Search for the First Kagay-anon Settlement - Hernandez, Vito Paolo C. (Hukay; Vol 7 (2005), 2016)
This paper advances the study of the Huluga Open Site's landscape using data from the 2004 Cagayan de Oro Archaeological Project. It briefly discusses what landscape archaeology is, and cites several examples of this kind of research in the Philippines. It then discusses hypotheses made from observations on the data studied. It concludes by offering new directions from overlooked data to finding Cagayan de Ora's first settlement.